ĐÁNH GIÁ KHẢ NĂNG PHÁT SINH ĐỘNG ĐẤT MẠNH Ở MIỀN BẮC VIỆT NAM - Hải, Đặng Thanh (Vietnam Journal of Earth Sciences, 2017)
This paper presents 6 seismogenic zones in the Northern part of Vietnam, based on the viewpoint of seismotectonic and the combination of the recently interpreters of geological, geophysical and geodynamic data.The modified first type Gumbel asymptotic distribution of extreme value can allow to issue the maximum magnitude preparedness earthquakes for each zone. ln the other hand, the time- magnitude predictable model can allow to caculate the probabilities of occurrence of strong· earthquakes in the six seismogenic zones (with magnitudes M5 = 5.0, 5.5 and 6.0) for the next 10, 20, 30 , 40 and 50 years (from 2002 year).